A design of movement detection security cameras using Arduino - Jerron, Bin Pius (Universiti Malaysia Sarawak (UNIMAS), 2017)
A camera is a useful facility and very common to the part of human life. Without camera, human are not able to create either bad or beautiful moments in their life. During this era of globalization, the development of cameras in this country had been increased from time to time. This is due to the change of technology and also human’s need especially when dealing with a living being. Although a single camera has improve its specification including their ability to capture a high quality image, increasing the memory storage, wired or wireless and many more, however most existing cameras are stationary. Hence, this project was introduce to make an improvement on how to make it moves clockwise or counter clockwise based to the pointed direction. This project will use the basic Pyroelectric Infrared (PIR) Sensor with the help of an Arduino microcontroller to detect the motion that occur within the specified range. The testing of the project including the human body, living and non-living objects which divided into five parts; detection of the different motion, temperature, surfaces, speed and distance.